Efektivitas Pemberian Kompres Hangat Cinnamomun Burmanni (Kayu Manis) Dan Cymbopogoncitratus (Serai) Terhadap Penurunan Nyeri Pada Pasien Gout Arthritis - Anita Ramadayani; Fatimah Khoirini; Almaini Almaini (Bajang Institute, 2026)
Background: The symptoms experienced by individuals with Gout Arthritis include severe pain in the toes, impaired function at the base of the big toe, the occurrence of hyperuricaemia, and the accumulation of uric acid crystals in the fluids and tissues. Continuous increases in uric acid levels will result in the deposition of monosodium urate crystals accumulating in the blood, and if not managed promptly, it will adversely affect the joints and other organs. The accumulation of crystals in the joints can trigger pain and swelling in various body joints, leading to deformities in the joints. Furthermore, high levels of uric acid can cause nephrolithiasis. Objective: To determine the effectiveness of warm cinnamon compresses and lemongrass compresses on pain in patients with gout arthritis. Method: The study employed a quasi-experimental design with a pretest–posttest design with a control group. The sample consisted of 76 respondents divided into two groups, namely 38 respondents in the warm cinnamon compress group and 38 respondents in the warm lemongrass compress group. The warm compress intervention was administered for two consecutive days. The research instruments used included the Numeric Rating Scale (NRS), observation sheets, and a respondent characteristics questionnaire. Results: Data analysis using the Wilcoxon Signed Rank Test with α ≤ 0.05 showed a p-value of 0.000, indicating a reduction and change in pain scale in both groups, and the Mann-Whitney test revealed that warm cinnamon compresses were more effective than warm lemongrass compresses in reducing pain from gout arthritis